Proposal for the Global Boundary Stratotype Section and Point (GSSP) for the Priabonian Stage (Eocene) at the Alano section (Italy) - Agnini, Claudia; Backman, Jan; Boscolo-Galazzo, Flavia; Condon, Daniel J.; Fornaciari, Eliana; Galeotti, Simone; Giusberti, Luca; Grandesso, Paolo; Lanci, Luca; Luciani, Valeria; Monechi, Simonetta; Muttoni, Giovanni; et al. (Episodes, 2021)
The base of the Priabonian Stage is one of two stage boundaries in the Paleogene that remains to be formalized. The Alano section (NE Italy) was elected by consensus as a suitable candidate for the base of the Priabonian during the Priabonian Working Group meeting held in Alano di Piave in June 2012. Further detailed research on the section is now followed by a formal proposal, which identifies the base of a prominent crystal tuff layer, the Tiziano bed, at meter 63.57 of the Alano section, as a suitable candidate for the Priabonian Stage. The choice of the Tiziano bed is appropriate from the historical point of view and several bio-magnetostratigraphic events are available to approximate this chronostratigraphic boundary and guarantee a high degree of correlatability over wide geographic areas. Events which approximate the base of the Priabonian Stage in the Alano section are the successive extinction of large acarininids and Morozovelloides (planktonic foraminifera), the Base of common and continuous Cribrocentrum erbae and the Top of Chiasmolithus grandis (nannofossils), as well as the Base of Subchron C17n.2n and the Base of Chron C17n (magnetostratigraphy). Cyclostratigraphic analysis of the Bartonian-Priabonian transition of the Alano section as well as radioisotopic data of the Tiziano tuff layer provide an absolute age (37.710 – 37.762 Ma, respectively) of this bed and, consequently, of the base of the Priabonian Stage.